A Model to Determine Optimally Hub Location for a Communication Network - Fibri Rakhmawati, Saib Suwilo, Sutarman, M. Zarlis (International Journal of Advanced Science and Technology, 2020)
The hub location can be considered as a particular type of a problem about how to locate facilities. The actual problem is defined as an assignment problem of locating hubs and the terminal nodes to these hubs. The aim of the problem is to find minimum cost of hub installation and the cost of routing the traffic in the communication network. There may also involve capacity restrictions on the amount of traffic that can transit by hubs. This paper discusses how to model the polyhedral properties of the problems and to address an approach of searching in the neighbourhood of a feasible solution.